Development of Photocatalytic Titanium Dioxide Shell on Titanium Powder for Cold Gas Dynamic Spray - Hawkins, Alexanna (Université d'Ottawa / University of Ottawa, 2026)
The objective of the thesis was to produce a titanium dioxide shell on spherical pure titanium powder that had heterojunctions of anatase and rutile nanostructures with photocatalytic properties for cold gas dynamic spray applications. This would be the first step in the global project of sprayable titanium dioxide coatings for self-sanitizing surfaces. A heterogeneous structure would provide the stability and closer band gap to the visible light spectrum from rutile and the high photocatalytic reactivity from anatase. The presence of heterojunctions could increase the photo-reactivity by promoting charge separations and promote reactions under visible light with a smaller band gap. Cold gas dynamic spray would provide the mechanism to consolidate this material without unwanted phase transformations from anatase to rutile at higher temperatures. As the temperatures are below the metals melting point, a combination of ceramic titanium dioxide and ductile titanium would assist in successful deposition via cold gas dynamic spray. Preliminary experiments were completed on readily available titanium plates to observe potential growths and compare the results to reference literature. The final powder production procedure included a hydrogen peroxide, melamine, and nitric acid chemical bath at 80 ℃ for twelve hours followed by calcination for one hour at 450 ℃. This experimental procedure yielded the growth of spiked nanorods with nanoflower aggregates seen through scanning electron imaging. X-ray diffraction verified the presence of anatase and rutile structures, and Raman spectroscopy verified the titanium dioxide shell was predominantly anatase near the titanium core, with anatase and rutile heterojunctions at the outer part of the titanium dioxide shell. Photocatalytic testing was completed by subjecting the titanium dioxide in deionized water to methylene blue, an organic dye commonly used as an indicator for evaluating photocatalytic performance, and an ultraviolet light source to produce reactive oxidizing species that accelerate the decomposition of methylene blue. The experimental powders photocatalytic reactivity was compared to that of two commercial powders, Altair and Neoxid. Methylene blue adsorption and subsequent decomposition by the powders was characterized through microplate light absorbancy readings. The experimentally produced powder performed comparable to the commercial powders, verifying its photocatalytic properties under ultraviolet light. Dynamic vapour sorption was completed on all three powders to characterize the surface areas and adsorption properties of the experimental and commercial powders to provide further understanding of photocatalytic results. The commercial powders had different particle size, specific surface areas, and dynamics of adsorption when compared to the experimental powder, which would impact photocatalytic behaviour. Although the experimental powder did not have superior photocatalytic reactivity to those of the commercial powders, the motivation is the presence of a ductile titanium core would plastically deform below its melting temperature to promote deposition efficiency in cold gas dynamic spray applications and produce a successful photocatalytic titanium dioxide coating. Solely ceramic titanium dioxide powders, like Altair and Neoxid, experience brittle impingement and poor deposition from lack of plastic deformation and metallurgical bonding. Overall, successful growth of heterogeneous titanium dioxide shells was grown on titanium powder that possessed photocatalytic properties comparable to commercially available powders to be applied in cold gas dynamic spray applications. The work completed created a strong foundation for project development and expansion.
Keywords: photocatalytic; titanium dioxide; cold gas dynamic spray; reactive oxidizing species; methylene blue; powder development; titanium; ultraviolet; photoreactivity